Adverse drug reactions in neonates: a brief analysis of the FDA adverse event reporting system - Byskov, Pernille Kähler; Baden, Christoffer Storm; Andersen, Jon Trærup; Jimenez-Solem, Espen; Olsen, Ramus Huan; Gade, Christina; Lausten-Thomsen, Ulrik (Frontiers in Pharmacology, 2024)
Introduction: Drug trials in neonates are scarce and consequently, neonates are at risks of adverse drug reactions (ADRs). Spontaneous ADR reporting is an important tool to expand knowledge and drug safety in neonates. This study explores the quality of the current neonatal ADR reports and the ADR reports of the most common drugs in the neonatal departments.Methods: An observational cross-sectional study focused on neonates, using data on spontaneous reports extracted from the U.S. Food and Drug Administration Adverse Events Reporting System (FAERS) from Q3 2014 until December 2022. Only primary suspect drugs given to age <30 days were included in the analysis.Results: Spontaneous reports from 13 million patients of all ages, totaling 50 million adverse drug reactions (ADRs), were evaluated. Information regarding age was missing in 40% of the reports, and data on just 43,737 neonates with 948 different suspect drugs were identified and included in the analyses. We reported frequency of spontaneous ADR reports in the FAERS database for the ten most frequently administrated drugs at the US neonatal intensive care units.An overall underreporting of neonatal ADRs is still present. The FAERS database in this current form insufficiently discriminates between pre-and postnatal drug exposure. Improved systems for neonatal pharmacovigilance isare urgently needed An overall underreporting of neonatal ADRs is still present.